The Part-Time Revolution: Changes in the Parenthood Effect on Women's Employment in Austria - Caroline Berghammer; Bernhard Riederer (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2018)
We compare employment rates of mothers and childless women over the life course across the birth cohorts from 1940 to 1979 in Austria. By following synthetic cohorts of mothers and childless women up to retirement age, we are able to study both short-term and long-term consequences of having a child. We consider employment participation as well as working time and also perform analyses by educational level. Our study is based on the Austrian microcensus (labour force survey), conducted between 1986 and 2016. The results show that although employment rates of mothers have increased across cohorts, the spread of part-time work has led to a declining work volume of mothers with young children. Return to the workplace is increasingly concentrated when the child is 3 to 5 years old. Part-time employment is primarily adopted (at least with younger children) by highly educated mothers and often remains a long-term arrangement.
Keywords: 300; Austria; education; family policy; female labour force participation; mothers' employment; part-time; work arrangements; working mothers